Workshop of Land Ink: contextualizing pigments in the discipline of History of Chemistry in LEdoC/UFMA - Meubles Borges Júnior; Matheus Casimiro Soares Ferreira; Carolina Pereira Aranha (Universidade Federal do Norte do Tocantins, 2018)
In addition to being an environmentally healthy and inexpensive technique, the production of land ink can be a facilitator in the teaching-learning process in science. This work presents an experience in the History of Chemistry, in a course in Licentiate in Rural Education, Federal University of Maranhão (UFMA-Bacabal), in which the central theme "the chemistry of pigments" was worked in a contextualized way. The contextualization of the content was carried out through the three categories of the contextualization process (punctual exemplification and motivational character, teaching-learning strategy, formation of critical citizen in decision-making), culminating in the development of a critical-reflective consciousness in the CTSA perspective. As methodological procedures were used: expository class; reading and interpretation of scientific articles; debates; land ink office; painting and exposition of ceramic artifacts; and evaluation. In this context, the land ink workshop gains featured because it brought scientific, technological and social contexts, contributing to the valorization and recovery of facts and experiences of everyday life, discussing and experiencing the meaning of sustainability, with technology and technique environmentally healthy and low thus increasing the potential of the teaching-learning process.